1995
DOI: 10.1056/nejm199511303332201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Alendronate on Bone Mineral Density and the Incidence of Fractures in Postmenopausal Osteoporosis

Abstract: Daily treatment with alendronate progressively increases the bone mass in the spine, hip, and total body and reduces the incidence of vertebral fractures, the progression of vertebral deformities, and height loss in postmenopausal women with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,138
8
63

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,129 publications
(1,267 citation statements)
references
References 30 publications
58
1,138
8
63
Order By: Relevance
“…Bisphosphonates are today's worldwide leading medication [7][8][9][10][11][12][13][14][15][16] and are recommended as first-line treatments for osteoporosis [1,2,17,18]. Two chemically distinct groups of bisphosphonates exist: Simple non-nitrogen-containing bisphosphonates (Non-N-BP's, e.g., Etidronate) and nitrogen-containing bisphosphonates (N-BP´s) e.g., Ibandronate, Alendronate, Zoledronate and Risedronate).…”
Section: Bisphosphonates Are the Most Common Therapy For Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphosphonates are today's worldwide leading medication [7][8][9][10][11][12][13][14][15][16] and are recommended as first-line treatments for osteoporosis [1,2,17,18]. Two chemically distinct groups of bisphosphonates exist: Simple non-nitrogen-containing bisphosphonates (Non-N-BP's, e.g., Etidronate) and nitrogen-containing bisphosphonates (N-BP´s) e.g., Ibandronate, Alendronate, Zoledronate and Risedronate).…”
Section: Bisphosphonates Are the Most Common Therapy For Osteoporosismentioning
confidence: 99%
“…There exists some evidence that branded Risedronate might be a slightly better suitable alternative bisphosphonate drug for gastrointestinal sensitive patients compared to original branded or generic Alendronate [7][8][9]32,33,[39][40][41][42][43][44][45][46]. Two recent studies have shown differences in tablets properties that might explain different rates of adverse events.…”
Section: Lower Bioavailability and Higher Rate Of Adverse Events Due mentioning
confidence: 99%
“…However, the changes in BMD explain only a fraction of the observed fracture risk reduction [5][6][7]. These observations suggest that anti-resorptive agents improve bone strength by decreasing bone turnover and by increasing intrinsic material properties of bone rather than simply affecting bone mass.…”
Section: Introductionmentioning
confidence: 97%
“…It reduced the risk of fracture by about 50% in patients with prevalent lowtrauma fracture [45]. Subsequently, three more BPs have been approved: risedronate, ibandronate, and zoledronic acid.…”
Section: Bisphosphonatesmentioning
confidence: 99%